PlGF Reduction Compromises Angiogenesis in Diabetic Foot Disease Through Macrophages - Zhu, Lingyan; Qian, Jieqi; Jiang, Yinan; Yang, Tianlun; Duan, Qiong; Xiao, Xiangwei (Frontiers in Immunology, 2021)
Diabetic foot disease (DFD) is a common and serious complication for diabetes and is characterized with impaired angiogenesis. In addition to the well-defined role of vascular endothelial growth factor (VEGF) -A and its defect in the pathogenesis of DFD, another VEGF family member, placental growth factor (PlGF), was also recently found to alter expression pattern in the DFD patients with undetermined mechanisms. This question was thus addressed in the current study. We detected attenuated PlGF upregulation in a mouse DFD model. In addition, the major cell types at the wound to express the unique PlGF receptor, VEGF receptor 1 (VEGFR1), were macrophages and endothelial cells. To assess how PlGF regulates DFD-associated angiogenesis, we injected recombinant PlGF and depleted VEGF1R specifically in macrophages by local injection of an adeno-associated virus (AAV) carrying siRNA for VEGFR1 under a macrophage-specific CD68 promoter. We found that the angiogenesis and recovery of the DFD were both improved by PlGF injection. The PlGF-induced improvement in angiogenesis and the recovery of skin injury were largely attenuated by macrophage-specific depletion of VEGF1R, likely resulting from reduced macrophage number and reduced M2 polarization. Together, our data suggest that¬ reduced PlGF compromises angiogenesis in DFD at least partially through macrophages.